Efektivitas Terapi Zikir terhadap Post Traumatic Stress Disorder (PTSD) pada Penyintas Tsunami Palu - Rannisa Muslaini; Nanum Sofia (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2020)
This study aims to determine the effectivity of dzikr on post traumatic stress disorder (PTSD) in Palu’s tsunami survivors on the past 2018. This research used experimental group and control group. Each groups consist of 5 participants. Dzikr training were given to the experimental group while control group were received the disaster education as placebo. The Impact of Event Scale-Revised (IES-R) was used to measure PTSD. Participants of this research were survivors of Palu’s tsunami, Muslims, lived in refugee barracs, and previously owned house near the coast. Based on anava mixed design analysis test, there is significant impact of dzikr training in experimental group compared to the control group with disaster education. Thus, Dzikr has been shown to reduce individual PTSD levels.